PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR PADA MATERI LINGKARAN DI SMPN 19 PONTIANAK - Suhendra, Martin; Mirza, Ade; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aimed  of this research were to know the study achievement after being taught by using Problem Based Learning (PBL) model on circle material and to know the effect on study achievement after being taught by using PBL model on Circle material of SMP N 19 Pontianak. The form of this research was quasy experimental study with nonequivalent control grup design. The sample of this research was class VIII F  as an experimental class and class VIII G as a control class. The technique of data collection was a measurement technique and the tool of data collection is a test in the form of essay test. The pretest data are analyzed by using t-test after fulfilling the homogeneity and normality test. The research finding showed that the mean score of pre-test is 5.82 while the mean score of post-test is 16.10. The result of t test was 0.00 with significance different 0.05 indicated that any differences between PBL and direct learning model on study achievement. The calculation of effect size was 2.75. it is higher than 0.8 and categorized as ?High?. It could be concluded that the using of PBL influences study achievement on circle material. Keywords:  Circle Material, Problem Based Learning Model, Students Achievement